Family History and Hypertension with Incidence of Diabetes Mellitus type II - Dewi Nurhanifah; Muhammad Ansari (Sean Institute, 2023)
Diabetes Mellitus is one infectious disease consequence happening. Disturbance of metabolism chronic be marked by height blood sugar levels. According to data from the 2019 International Diabetes Federation, Indonesia is included in the top 10 countries with amount sufferer supreme and is the only Southeast Asian country in that list. Study This aim is to know the connection between history discharge and hypertension with incident Diabe test mellitus type II in the Village Malintang Subdistrict Peat Banjarmasin Regency. The research design used is observational analytics with approach case-control. Sample research of as many as 48 people consists of 16 cases and 32 controls taken with a simple random sampling technique. Analysis of data using the Chi-Square test. Research Results pointing right There is a connection between history family with the incidence of Diabetes Mellitus type II with value p=0.001 OR=11.074, there is a connection between hypertension with the incidence of Diabetes Mellitus type II with bro value p=0.004, OR=7.857. Conclusion in the study: There is a connection between family history and hypertension with the incidence of Diabetes Mellitus type II.